Peningkatan Kesiapan Belajar Fisik Siswa Sekolah Dasar Dengan Metode Penapisan Yoga Asanas - Perbowosari, Heny; Prima Dewi PF, Kadek Aria; Sudarsana, I Ketut; Budi Wijaya, I Komang Wisnu (Jurnal Penelitian Agama Hindu, 2021)
The purpose of this study is to describe the ability of the Yoga Asanas screening method in improving students' physical learning readiness. This research used a pre-experimental design with One Group Pretest-Posttest Design. The population were the elementary school students (SD) in Bali. Simple random sampling was used in collecting the samples. Learning readiness observation sheets were used as the research instruments. Further, the data were analyzed descriptively using a normalized score gain technique. The results showed that Yoga Asanas screening method was able to improve children's physical readiness to learn (g = 0.87 (height)).